2016
DOI: 10.3126/hren.v13i3.17965
|View full text |Cite
|
Sign up to set email alerts
|

The effect of birth interval on fetal outcomes

Abstract: Background: Perinatal mortality includes both deaths in the first week of life and fetal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Short birth interval is a universal public health problem having association with adverse maternal, fetal, neonataland child outcomes such as low birth weight and perinatal death [4,5], preterm delivery, small for gestational age [6], admission to neonatal intensive care unit [7], stillbirth, abortion, neonatal mortality [8], infant and under-5 mortality [8,9], infant/child malnutrition including underweight, wasting, stunting [8,10], neurodevelopmental and intellectual delay, autism, cerebral palsy [11], gestational diabetes [8,12], precipitous labor [7], anemia [8,13], uterine rupture, premature rupture of membrane, preeclampsia and chronic hypertension [8,14,15]. Most of these studies [4][5][6][7][9][10][11][12][13][14][15] don't show causal association between short birth interval and the aforementioned pregnancy outcomes. Furthermore, the reported associations might have been largely attributed to confounding effects by genetically heritable familial factors [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Short birth interval is a universal public health problem having association with adverse maternal, fetal, neonataland child outcomes such as low birth weight and perinatal death [4,5], preterm delivery, small for gestational age [6], admission to neonatal intensive care unit [7], stillbirth, abortion, neonatal mortality [8], infant and under-5 mortality [8,9], infant/child malnutrition including underweight, wasting, stunting [8,10], neurodevelopmental and intellectual delay, autism, cerebral palsy [11], gestational diabetes [8,12], precipitous labor [7], anemia [8,13], uterine rupture, premature rupture of membrane, preeclampsia and chronic hypertension [8,14,15]. Most of these studies [4][5][6][7][9][10][11][12][13][14][15] don't show causal association between short birth interval and the aforementioned pregnancy outcomes. Furthermore, the reported associations might have been largely attributed to confounding effects by genetically heritable familial factors [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…From bivariable analysis, it has been shown that neonates born to mothers with birth spacing of < 2 years were 1.89 times more likely to be asphyxiated as compared to those with ≥2 years of birth spacing. This may be due to the fact that narrow birth spacing (< 2 years) is a universal public health problem having association with adverse maternal, fetal and neonatal outcomes such as low birth weight 56 , 57 , preterm delivery, small for gestational age 58 , precipitous labor 59 , gestational diabetes 60 , 61 , anemia 61 , 62 , uterine rupture, premature rupture of membrane, preeclampsia and chronic hypertension 60 , 63 , 64 . Significance of some of these outcomes is also supported by this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, quality of intrapartum care during labor and delivery has been recognized as the single most important predictor of the overall morbidity and mortality from asphyxia neonatorum 32 , 34 , 36 – 49 . More specifically, factors like antenatal obstetric complications 17 , 20 , 40 , 42 , 49 , 51 56 , parity 19 , 42 , multiple births 22 , gestational age <37 or >41 weeks 22 , 42 , low birth weight 18 , 40 , 41 , 42 , premature rupture of membranes 20 , 44 , 45 , 48 , prolonged labor 18 , 19 , 41 , 42 and fetal distress 40 , 41 , 48 , 49 have already been identified to be among the risk factors of asphyxia neonatorum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a short birth interval is an important public health concern, as it comes with a host of adverse effects on mothers and their children ( Thapaliya et al, 2015 ). The majority of neonatal and maternal deaths occurred in sub-Saharan Africa and South Asia, which comprised 3.1 million neonatal deaths and 287, 000 maternal deaths ( Thapaliya et al, 2015 ; WHO, UNICEF, UNFPA, 2019 ).Ethiopian mini Demographic and Health Survey (EDHS) showed that there is still a high (59%) under-five mortality rate and 33% neonatal death ( Mini EDHS, 2019 ). Moreover, there are 412 maternal deaths per 100,000 live births women ( EDHS, 2016 ).…”
Section: Introductionmentioning
confidence: 99%